Praktek Nikah Paksa di Desa Cibeureum Kabupaten Ciamis - Anis Aljalis Rahmah; Sumadi Sumadi; Rudi Rudi (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2019)
This research is motivated by the low knowledge about the importance of involving children in choosing a partner for themselves and determining their readiness for marriage, both mental and material readiness. And to inform the public that marriage on the basis of coercion is included in domestic violence. The research method used is the field research method, in which this research focuses on the results of data collection from predetermined informants. While the data collection techniques used were interviews, observation and documentation. After conducting the research, the results obtained were parents who forcibly married their children to reduce their burden materially and responsibly. Because children who are already married they consider it no longer their responsibility